Dynamic and static mechanical measurements of flux-lattice softening and associated hysteretic depinning dissipation peak in YBa2Cu3Ox ceramic - D'Anna, G.; Benoit, W.; Luzuriaga, J.; Berger, H. (IOP Publishing, 1990)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina